A foamed nickel loaded nickel-iron alloy / yttrium trioxide composite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202410520753.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-28
AI Technical Summary
上述方法均是有效的,但是对于催化性能的改善仍有待提高
[0020]本发明制得的泡沫镍负载的镍铁合金/三氧化二钇NiFe/Y2O3复合材料具有丰富的NiFe-Y2O3异质界面,该界面促进了水分子的解离,而界面处的电子转移改善了NiFe合金过强的H吸附能,从而使NiFe合金的HER性能得到了极大改善,表现出与商用Pt/C相当的催化活性及优异的稳定性。
Smart Images

Figure CN118416898B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, and more particularly to a nickel-iron alloy / yttrium oxide composite material supported on nickel foam, its preparation method, and its application as a catalyst in alkaline hydrogen evolution reaction. Background Technology
[0002] Hydrogen, as an important raw material in the chemical industry, has wide applications in petroleum refining, ammonia synthesis, and methanol synthesis. More importantly, hydrogen possesses advantages such as being clean and pollution-free, and having high energy density, making it a highly promising energy carrier and a chemical most likely to replace fossil fuels. Unlike methods of obtaining hydrogen from traditional fossil fuels, the electrocatalytic hydrogen evolution reaction (HER) has become a promising hydrogen production method due to its simplicity and environmental friendliness. However, the adsorption and dissociation of water on the catalyst surface, and the subsequent adsorption of hydrogen (H₂O), present challenges. ad Due to the high energy barrier of hydrogen desorption and the resulting hydrogen, the HER kinetics in alkaline electrolytes are particularly slow. Therefore, developing efficient and low-cost alkaline HER catalysts to improve their reaction kinetics is of great significance for promoting the practical application of hydrogen production by water electrolysis. Among many non-precious metal materials, NiFe alloys have received widespread attention and exploration due to their low cost, excellent conductivity, and good alkaline HER activity. However, there are still some problems with NiFe alloys as HER catalysts, mainly: (1) single-component NiFe alloys lack effective water dissociation sites, which is not conducive to the supply of protons for subsequent reactions; (2) the H adsorption energy of NiFe alloys is too strong, which leads to H adsorption. ad The conversion kinetics to hydrogen are slow.
[0003] To improve the catalytic performance of NiFe alloys, researchers have conducted extensive studies and achieved certain results. According to literature reports, the H adsorption energy of NiFe alloys can be effectively controlled by introducing other metal elements for alloying and adjusting the alloy composition; the dissociation of water molecules can be accelerated by constructing composite materials to introduce water dissociation components. While these methods are effective, further improvements in catalytic performance are needed. This invention designs and prepares a NiFe / Y₂O₃ composite material with abundant metal-rare earth oxide interfaces using a heterostructure engineering strategy. The NiFe-Y₂O₃ heterostructure promotes water molecule dissociation, and the redistribution of charge at the interface optimizes the H adsorption energy of the NiFe alloy. The synergistic effect of these two factors achieves rapid HER kinetics, thereby improving catalytic performance. Summary of the Invention
[0004] To overcome the shortcomings of the prior art, the present invention provides a nickel-iron alloy / yttrium oxide composite material supported by nickel foam, its preparation method and application.
[0005] According to a first aspect of this disclosure, a method for preparing a nickel-iron alloy / yttrium oxide composite material supported on nickel foam is provided, characterized by comprising the following steps:
[0006] (1) According to the hydrothermal method, nickel foam-supported nickel-iron-yttrium hydroxide precursor was synthesized by first dissolving 0.16-0.22 g of nickel nitrate hexahydrate, 0.05-0.07 g of ferrous acetate, 0.15-0.24 g of yttrium nitrate hexahydrate and 0.26-0.30 g of hexamethylenetetramine in a mixed solution of anhydrous ethanol and deionized water, respectively, and stirring evenly with a magnetic stirrer. Then, nickel foam was added to carry out hydrothermal reaction. The sample after hydrothermal reaction was washed and dried to obtain nickel-iron-yttrium hydroxide precursor.
[0007] (2) Nickel-iron alloy / yttrium oxide (NiFe / Y2O3) composite material is prepared by annealing thermal reduction treatment. The nickel-iron yttrium hydroxide precursor is placed in a tube furnace and calcined in a 3% to 10% H2 / Ar atmosphere to convert it into nickel-iron alloy / yttrium oxide (NiFe / Y2O3) composite material.
[0008] Preferably, in step (1), the hydrothermal reaction uses a mixed solution of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol is 1:1.
[0009] Preferably, in step (1), the hydrothermal reaction temperature is 90-120°C and the reaction time is 8-12h.
[0010] Preferably, in step (2), the precursor is subjected to the annealing treatment in an H2 / Ar atmosphere, with a heating rate of 1–5 °C / min. -1 The calcination temperature is 400-550℃ and the calcination time is 1-5h. Nickel-iron hydroxide is transformed into NiFe alloy, yttrium hydroxide is transformed into Y2O3, and the precursor is transformed into NiFe / Y2O3 composite material.
[0011] According to a second aspect of this disclosure, a nickel-iron alloy / yttrium oxide composite material supported on nickel foam is provided.
[0012] According to a third aspect of this disclosure, an application of a nickel-iron alloy / yttrium oxide composite material supported on nickel foam is provided, characterized in that the composite material is used as a catalyst for electrochemical activation and testing.
[0013] Preferably, the electrochemical activation and testing are performed using the nickel-supported nickel-iron alloy / yttrium oxide composite material as a catalyst, including the following steps:
[0014] (1) The electrochemical test was performed in a standard three-electrode test system, wherein the nickel-coated nickel-iron alloy / yttrium oxide (NiFe / Y2O3) composite material was directly used as the working electrode, and the area of the working electrode was 0.25–2 cm². 2 A carbon rod is used as the counter electrode, a silver / silver chloride electrode is used as the reference electrode, and a KOH solution with a concentration of 0.8–1.2 M is used as the electrolyte.
[0015] (2) Before performing the electrochemical test, the working electrode was activated by cyclic voltammetry at a scan rate of 20–80 mV / s. -1 The voltage scanning range relative to the reversible hydrogen electrode is 0 to -0.5V, and the number of scans is 5 to 50.
[0016] (3) The voltage scan range for polarization curve testing relative to the reversible hydrogen electrode is 0 to -0.8V, and the scan rate is 5mVs. -1 Electrochemical impedance spectroscopy (EIS) measurements were performed at a constant voltage of -0.15 V relative to the reversible hydrogen electrode, with a frequency range of 0.01 Hz to 100 kHz. For double-layer capacitance measurements, the voltage scan range relative to the silver / silver chloride electrode was -0.45 V to -0.35 V, with scan rates of 20, 30, 40, 50, 60, 70, and 80 mV s. -1 .
[0017] The purpose of this invention is:
[0018] This invention provides a nickel-iron alloy / yttrium oxide (NiFe / Y₂O₃) composite material with abundant metal-rare earth oxide interfaces, its preparation method, and its applications. The material is prepared via a simple hydrothermal method followed by thermal reduction. It exhibits a nanosheet morphology composed of numerous interconnected nanoparticles, possessing a large specific surface area and exposing more active sites, which is beneficial for electrolyte penetration and bubble diffusion. The abundant NiFe-Y₂O₃ heterostructure promotes water molecule dissociation, and electron transfer at the interface improves the excessively strong H adsorption energy of the NiFe alloy. Therefore, the synergistic effect of the NiFe alloy and Y₂O₃ at the interface accelerates the alkaline HER kinetics, thereby improving catalytic performance. This material shows promising application potential as a HER catalyst. This invention is expected to inspire the application of rare earth oxides in the field of water electrolysis catalysis.
[0019] The beneficial effects of this invention are:
[0020] The nickel-iron alloy / yttrium oxide (NiFe / Y2O3) composite material prepared by this invention has abundant NiFe-Y2O3 heterostructures. These interfaces promote the dissociation of water molecules, and the electron transfer at the interface improves the excessively strong H adsorption energy of the NiFe alloy. As a result, the HER performance of the NiFe alloy is greatly improved, exhibiting catalytic activity comparable to that of commercial Pt / C and excellent stability. Attached Figure Description
[0021] The above and other features, advantages, and aspects of embodiments of the present invention will become more apparent from the accompanying drawings and the following detailed description. The drawings are provided for a better understanding of the invention and are not intended to limit the invention. In the drawings, the same or similar reference numerals denote the same or similar elements, wherein:
[0022] Figure 1 The polarization curves of the nickel-iron alloy / yttrium oxide (NiFe / Y2O3) prepared in Example 1 of this invention and the NiFe alloy prepared in the comparative example are compared with those of commercial Pt / C.
[0023] Figure 2 The XRD patterns of the nickel-iron alloy / yttrium oxide (NiFe / Y2O3) prepared in Example 1 of this invention and the NiFe alloy and Y2O3 prepared in the comparative example.
[0024] Figure 3 SEM images of the nickel-iron alloy / yttrium trioxide (NiFe / Y2O3) foam supported on nickel prepared in Example 1 of this invention.
[0025] Figure 4 TEM image of the nickel-iron alloy / yttrium oxide (NiFe / Y2O3) supported on nickel foam prepared in Example 1 of this invention.
[0026] Figure 5 TEM images of the nickel-supported NiFe alloy foam prepared in the comparative example of this invention.
[0027] Figure 6 SAED spectrum of nickel-iron alloy / yttrium trioxide (NiFe / Y2O3) supported on nickel foam prepared in Example 1 of this invention.
[0028] Figure 7 HRTEM image of the nickel-iron alloy / yttrium oxide (NiFe / Y2O3) foam supported on nickel prepared in Example 1 of this invention.
[0029] Figure 8 XPS full spectra of the nickel-iron alloy / yttrium oxide NiFe / Y2O3 foam supported by nickel in Example 1 of this invention and the NiFe alloy prepared in the comparative example.
[0030] Figure 9 The Ni 2p spectra of the nickel-iron alloy / yttrium oxide NiFe / Y2O3 supported on nickel foam prepared in Example 1 of this invention and the NiFe alloy prepared in the comparative example.
[0031] Figure 10 The Fe 2p spectra of the nickel-iron alloy / yttrium trioxide NiFe / Y2O3 supported on nickel foam prepared in Example 1 of this invention and the NiFe alloy prepared in the comparative example.
[0032] Figure 11 Y 3d spectra of nickel-iron alloy / yttrium trioxide NiFe / Y2O3 and Y2O3 prepared in Example 1 of this invention.
[0033] Figure 12 The Tafel curve comparison between the nickel-iron alloy / yttrium oxide (NiFe / Y2O3) foamed nickel-supported alloy prepared in Example 1 of this invention and the commercial Pt / C.
[0034] Figure 13 The capacitance current density versus scan rate curves of the nickel-iron alloy / yttrium oxide NiFe / Y2O3 foam supported on nickel in Example 1 of this invention and the NiFe alloy prepared in the comparative example.
[0035] Figure 14 The current density of the nickel-iron alloy / yttrium trioxide NiFe / Y2O3 foam supported in Example 1 of this invention and the NiFe alloy prepared in the comparative example are normalized to the electrochemical active area curve.
[0036] Figure 15 Chronopotential diagram of nickel-iron alloy / yttrium oxide (NiFe / Y2O3) supported on nickel foam prepared in Example 1 of this invention.
[0037] Figure 16 SEM images of the nickel-iron alloy / yttrium trioxide (NiFe / Y2O3) foamed nickel-loaded nickel-iron alloy prepared in Example 1 of this invention after chronopotential testing.
[0038] Figure 17 TEM images of the nickel-iron alloy / yttrium trioxide (NiFe / Y2O3) foamed nickel-loaded alloy prepared in Example 1 of this invention after chronopotential testing.
[0039] Figure 18 TEM image of the nickel-iron alloy / yttrium oxide (NiFe / Y2O3) foam supported on nickel prepared in Example 2 of this invention.
[0040] Figure 19TEM image of the nickel-iron alloy / yttrium oxide (NiFe / Y2O3) supported on nickel foam prepared in Example 3 of this invention. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Embodiments 2 and 3 of the present invention are similar to Embodiment 1, and Embodiment 1 will be used as an example for detailed description.
[0042] Example 1
[0043] The preparation method of the nickel-iron alloy / yttrium oxide composite material supported on nickel foam in this embodiment includes the following steps:
[0044] (1) The nickel-iron-yttrium hydroxide precursor supported on nickel foam was synthesized by hydrothermal method. First, 0.1919 g of nickel nitrate hexahydrate, 0.0574 g of ferrous acetate, 0.1915 g of yttrium nitrate hexahydrate and 0.2804 g of hexamethylenetetramine were dissolved in a mixed solution of anhydrous ethanol and deionized water and stirred with a magnetic stirrer for 30 min. Then, nickel foam was added to carry out a hydrothermal reaction at a reaction temperature of 100 °C for 10 h. The sample after the reaction was washed and dried to obtain the nickel-iron-yttrium hydroxide precursor.
[0045] (2) NiFe / Y2O3 composite material was prepared by annealing thermal reduction treatment. The nickel-iron-yttrium hydroxide precursor was placed in a tube furnace and calcined under a 5% H2 / Ar atmosphere at a heating rate of 2℃ min. -1 The calcination temperature is 450℃ and the calcination time is 2h, which transforms it into a NiFe / Y2O3 composite material.
[0046] In some embodiments, the application of the nickel-supported nickel-iron alloy / yttrium oxide composite material as a catalyst for electrochemical activation and testing includes:
[0047] The prepared nickel-foamed NiFe / Y2O3 composite material was directly used as the working electrode, with an area of 0.5 cm². 2 Before conducting electrochemical tests, the working electrode was activated using cyclic voltammetry at a scan rate of 50 mV / s. -1 The voltage scanning range relative to the reversible hydrogen electrode is 0 to -0.5V, and the number of scans is 50.
[0048] In some embodiments, the application of the nickel-supported nickel-iron alloy / yttrium oxide composite material as a catalyst for electrochemical activation and testing includes: testing the activated working electrode on an Ivium-n-Stat electrochemical workstation, with the polarization curve measured relative to the reversible hydrogen electrode at a voltage scan range of 0 to -0.8 V and a scan rate of 5 mV s. -1 Electrochemical impedance spectroscopy (EIS) measurements were performed at a constant voltage of -0.15 V relative to the reversible hydrogen electrode, with a frequency range of 0.01 Hz to 100 kHz. For double-layer capacitance measurements, the voltage scan range relative to the silver / silver chloride electrode was -0.45 V to -0.35 V, with scan rates of 20, 30, 40, 50, 60, 70, and 80 mV s. -1 .
[0049] Comparative Example
[0050] Based on Example 1, without adding yttrium hexahydrate in step (1) and keeping other conditions unchanged, a nickel-supported NiFe alloy and its use as a HER catalyst can be obtained.
[0051] Morphological and structural characterization of NiFe alloy and NiFe / Y2O3:
[0052] Figure 2 The XRD diffraction patterns of NiFe / Y₂O₃ and NiFe and Y₂O₃ are shown. The three diffraction peaks at 44.1°, 51.3°, and 75.3° correspond to the (111), (200), and (220) crystal planes of the NiFe alloy, respectively. The diffraction peak at 29.1° corresponds to the (222) crystal plane of Y₂O₃, indicating that the prepared catalyst is a mixed phase containing NiFe alloy and Y₂O₃. Figure 3 and Figure 4 The images show scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of NiFe / Y2O3, respectively. It can be seen that the prepared NiFe / Y2O3 exhibits a nanosheet morphology composed of interconnected nanoparticles, with an average nanoparticle size of approximately 14 nm. Figure 5 The TEM image of the single-component NiFe alloy prepared for comparison shows a morphology similar to NiFe / Y₂O₃, but with larger nanoparticles, averaging approximately 55 nm. This indicates that the addition of Y₂O₃ prevents catalyst sintering during annealing, thereby reducing nanoparticle size and resulting in a larger specific surface area and more active sites. Figure 6The selected area electron diffraction (SAED) pattern of NiFe / Y2O3 is shown. The smallest diffraction ring in the figure corresponds to the (222) crystal plane of Y2O3, and the remaining series of diffraction rings correspond to the (111), (200), (220), (311) and (331) crystal planes of NiFe alloy, which is consistent with the XRD results. Figure 7 The image shows a high-resolution TEM (HRTEM) image of NiFe / Y₂O₃. The interplanar spacing of 0.308 nm corresponds to the (222) crystal plane of Y₂O₃, while the lattice fringes with interplanar spacings of 0.180 nm and 0.207 nm correspond to the (200) and (111) crystal planes of the NiFe alloy, respectively. More importantly, a clear interface exists between the NiFe alloy and Y₂O₃, indicating that a NiFe / Y₂O₃ composite material with a rich metal-rare earth oxide interface has been successfully prepared. Figure 8 The images show the XPS full spectra of NiFe alloy and NiFe / Y2O3. It can be seen that NiFe / Y2O3 contains Ni, Fe, Y, O, and C elements, while the NiFe alloy contains only Ni, Fe, O, and C elements, indicating the successful introduction of Y. Figure 9 and Figure 10 High-resolution XPS spectra of Ni 2p and Fe 2p for NiFe alloy and NiFe / Y2O3, respectively. In the Ni 2p spectrum, the characteristic peaks at 852.3 and 869.5 eV correspond to Ni 2p and Fe 2p, respectively. 0 2p 3 / 2 and Ni 0 2p 1 / 2 This indicates that Ni exists primarily in the metallic state. Furthermore, the peaks at 855.2 and 872.9 eV are attributed to Ni. 2+ 2p 3 / 2 and Ni 2+ 2p 1 / 2 The characteristic peaks are due to the interaction between Ni in the NiFe alloy and O in Y₂O₃ at the interface, as well as the inevitable oxidation in air. In the Fe 2p high-resolution spectrum, the three pairs of characteristic peaks with binding energies at 706.6 and 719.5, 709.2 and 722.8, and 710.5 and 724.2 eV correspond to Fe, respectively. 0 2p 3 / 2 and Fe 0 2p 1 / 2 Fe 2+ 2p 3 / 2 and Fe 2+ 2p 1 / 2 and Fe 3+ 2p 3 / 2 and Fe 3+ 2p 1 / 2The broad peak at 711.8 eV can be attributed to the Ni LMM Auger peak due to the relatively low Fe content in NiFe / Y2O3. Figure 11 The Y 3d spectra of NiFe / Y2O3 and Y2O3 are located at 156.7 (3d). 5 / 2 ) and 158.8 (3d 3 / 2 The characteristic peak of )eV corresponds to Y2O3, while the peak at 158.1 (3d) is located at 158.1 (3d) 5 / 2 ) and 160.2 (3d 3 / 2 The pair of characteristic peaks at )eV are attributed to yttrium carbonate. It is worth noting that, compared to single-component NiFe alloys, NiFe / Y₂O₃ Ni… 0 2p 3 / 2 and Fe 0 2p 3 / 2 The characteristic peaks shifted to lower binding energy positions by 0.2 and 0.3 eV, respectively. Compared to Y₂O₃, the Y₃d₂ of NiFe / Y₂O₃... 5 / 2 The characteristic peak shifted by 0.3 eV towards higher binding energy. These results indicate a strong electronic interaction between the NiFe alloy and Y₂O₃ at the abundant interface, meaning that the introduction of Y₂O₃ leads to a redistribution of interfacial charge and electron enrichment at Ni and Fe sites.
[0053] The catalytic performance of NiFe / Y2O3 was characterized at room temperature:
[0054] Electrochemical experiments were conducted using a standard three-electrode testing system. Figure 1 The figures show the HER polarization curves of NiFe / Y₂O₃, NiFe alloy, and commercial Pt / C catalyst in 1M KOH solution. It can be seen that the single-component NiFe alloy exhibits poor catalytic activity due to the lack of effective water dissociation sites and excessively strong H adsorption energy, particularly at a current density of 10 mA / cm⁻¹. -2 The overpotential is 145 mV. Compared to NiFe alloy, the NiFe / Y2O3 composite catalyst prepared by introducing Y2O3 shows significantly improved HER activity, requiring only 27 mV overpotential to drive a 10 mA cm⁻¹. -2 The current density is close to that of the Pt / C catalyst (21 mV). Furthermore, we can see that NiFe / Y₂O₃ achieves a current density of 100 mA cm⁻¹. -2 The overpotential is 103 mV, and its catalytic activity has exceeded that of Pt / C (106 mV). Figure 12 For the corresponding Tafel curves, the Tafel slopes for NiFe / Y₂O₃, NiFe alloy, and commercial Pt / C catalyst are 52, 86, and 42 mV dec, respectively. -1NiFe / Y2O3 has a smaller Tafel slope than NiFe alloys, indicating that it has faster HER kinetics. Figure 13 The figure shows the capacitance current density versus scan rate for NiFe / Y₂O₃ and NiFe alloys. The slope of the curve reflects the magnitude of the double-layer capacitance. As shown in the figure, the double-layer capacitances of NiFe / Y₂O₃ and NiFe alloy are 12.67 mF / cm² and 4.09 mF / cm², respectively. -2 The electrochemical active area is positively correlated with the double-layer capacitance and is often used to calculate the number of active sites on a catalyst. Therefore, NiFe / Y₂O₃ has a larger electrochemical active area, which leads to better catalytic activity. Figure 14 The curves obtained by normalizing the current density to the electrochemical active area represent the intrinsic activity of different catalysts. As can be seen from the figure, the current density achieved by NiFe / Y₂O₃ at a reversible hydrogen electrode voltage of -0.2V is 2.37 mA cm⁻¹. -2 ECSA This is far higher than that of NiFe alloy (0.42cm). -2 ECSA This indicates that NiFe / Y₂O₃ exhibits higher intrinsic catalytic activity than NiFe alloy. These results demonstrate that introducing Y₂O₃ into NiFe alloy through the construction of a NiFe / Y₂O₃ composite catalyst not only increases the number of active sites but also enhances its intrinsic catalytic activity, thereby resulting in superior HER activity. Figure 15 NiFe / Y2O3 at 1000 mA cm -2 Chronopotential curves at constant current density. As shown in the figure, after continuous operation in 1M KOH for 200 h, the overpotential increased by only 32 mV, indicating its excellent electrochemical stability and good application potential. Figure 16 and 17 The SEM and TEM images of NiFe / Y2O3 after 200h chronopotential testing show that the nanosheet structure composed of interconnected nanoparticles is well maintained, and the individual nanoparticles are clearly distinguishable, confirming that NiFe / Y2O3 has good structural stability.
[0055] Example 2
[0056] The preparation method of the nickel-iron alloy / yttrium oxide composite material supported on nickel foam in this embodiment includes the following steps:
[0057] (1) The nickel-iron-yttrium hydroxide precursor supported on nickel foam was synthesized by hydrothermal method. First, 0.1919 g of nickel nitrate hexahydrate, 0.0574 g of ferrous acetate, 0.2298 g of yttrium nitrate hexahydrate and 0.2804 g of hexamethylenetetramine were dissolved in a mixed solution of anhydrous ethanol and deionized water and stirred with a magnetic stirrer for 30 min. Then, nickel foam was added to carry out a hydrothermal reaction at 100 °C for 10 h. The sample after the reaction was washed and dried to obtain the nickel-iron-yttrium hydroxide precursor.
[0058] (2) NiFe / Y2O3 composite material was prepared by annealing thermal reduction treatment. The nickel-iron-yttrium hydroxide precursor was placed in a tube furnace and calcined under a 5% H2 / Ar atmosphere at a heating rate of 2℃ min. -1 The calcination temperature is 450℃ and the calcination time is 2h, which transforms it into a NiFe / Y2O3 composite material.
[0059] In some embodiments, the application of the nickel-supported nickel-iron alloy / yttrium oxide composite material as a catalyst for electrochemical activation and testing includes:
[0060] The prepared nickel-foamed NiFe / Y2O3 composite material was directly used as the working electrode, with an area of 0.5 cm². 2 Before conducting electrochemical tests, the working electrode was activated using cyclic voltammetry at a scan rate of 50 mV / s. -1 The voltage scanning range relative to the reversible hydrogen electrode is 0 to -0.5V, and the number of scans is 50.
[0061] In some embodiments, the application of the nickel-supported nickel-iron alloy / yttrium oxide composite material as a catalyst for electrochemical activation and testing includes:
[0062] The activated working electrode was tested on an Ivium-n-Stat electrochemical workstation. The polarization curve was measured relative to the reversible hydrogen electrode over a voltage scan range of 0 to -0.8 V at a scan rate of 5 mV / s. -1 Electrochemical impedance spectroscopy (EIS) measurements were performed at a constant voltage of -0.15 V relative to the reversible hydrogen electrode, with a frequency range of 0.01 Hz to 100 kHz. For double-layer capacitance measurements, the voltage scan range relative to the silver / silver chloride electrode was -0.45 V to -0.35 V, with scan rates of 20, 30, 40, 50, 60, 70, and 80 mV s. -1 .
[0063] The TEM image of NiFe / Y2O3 obtained in Example 2 is as follows. Figure 18As shown in the figure, the composite material prepared in Example 2 has a similar morphology to the material prepared in Example 1, that is, a nanosheet morphology composed of interconnected nanoparticles.
[0064] Example 3
[0065] The preparation method of the nickel-iron alloy / yttrium oxide composite material supported on nickel foam in this embodiment includes the following steps:
[0066] (1) The nickel-iron-yttrium hydroxide precursor supported on nickel foam was synthesized by hydrothermal method. First, 0.1919 g of nickel nitrate hexahydrate, 0.0574 g of ferrous acetate, 0.1532 g of yttrium nitrate hexahydrate and 0.2804 g of hexamethylenetetramine were dissolved in a mixed solution of anhydrous ethanol and deionized water and stirred with a magnetic stirrer for 30 min. Then, nickel foam was added to carry out hydrothermal reaction at a reaction temperature of 100 °C for 10 h. The sample after reaction was washed and dried to obtain the nickel-iron-yttrium hydroxide precursor.
[0067] (2) NiFe / Y2O3 composite material was prepared by annealing thermal reduction treatment. The nickel-iron-yttrium hydroxide precursor was placed in a tube furnace and calcined under a 5% H2 / Ar atmosphere at a heating rate of 2℃ min. -1 The calcination temperature is 450℃ and the calcination time is 2h, which transforms it into a NiFe / Y2O3 composite material.
[0068] In some embodiments, the application of the nickel-supported nickel-iron alloy / yttrium oxide composite material as a catalyst for electrochemical activation and testing includes:
[0069] The prepared nickel-foamed NiFe / Y2O3 composite material was directly used as the working electrode, with an area of 0.5 cm². 2 Before conducting electrochemical tests, the working electrode was activated using cyclic voltammetry at a scan rate of 50 mV / s. -1 The voltage scanning range relative to the reversible hydrogen electrode is 0 to -0.5V, and the number of scans is 50.
[0070] In some embodiments, the application of the nickel-supported nickel-iron alloy / yttrium oxide composite material as a catalyst for electrochemical activation and testing includes:
[0071] The activated working electrode was tested on an Ivium-n-Stat electrochemical workstation. The polarization curve was measured relative to the reversible hydrogen electrode over a voltage scan range of 0 to -0.8 V at a scan rate of 5 mV / s. -1Electrochemical impedance spectroscopy (EIS) measurements were performed at a constant voltage of -0.15 V relative to the reversible hydrogen electrode, with a frequency range of 0.01 Hz to 100 kHz. For double-layer capacitance measurements, the voltage scan range relative to the silver / silver chloride electrode was -0.45 V to -0.35 V, with scan rates of 20, 30, 40, 50, 60, 70, and 80 mV s. -1 .
[0072] The TEM image of NiFe / Y2O3 obtained in Example 3 is as follows. Figure 19 As shown in the figure, the composite material prepared in Example 3 has a similar morphology to the materials prepared in Examples 1 and 2, namely, a nanosheet morphology composed of interconnected nanoparticles.
[0073] In summary, the nickel-iron alloy / yttrium oxide (NiFe / Y₂O₃) composite material with abundant metal-rare earth oxide interfaces provided by this invention is prepared via a simple hydrothermal method followed by thermal reduction. This material exhibits a nanosheet morphology composed of numerous interconnected nanoparticles, possessing a large specific surface area and exposing more active sites, which is beneficial for electrolyte penetration and bubble diffusion. The abundant NiFe-Y₂O₃ heterostructure promotes the dissociation of water molecules, and the electron transfer at the interface improves the excessively strong H adsorption energy of the NiFe alloy. Therefore, the synergistic effect of the NiFe alloy and Y₂O₃ at the interface accelerates the alkaline HER kinetics, thereby improving catalytic performance and exhibiting catalytic activity comparable to commercial Pt / C and excellent stability.
[0074] The above embodiments are preferred embodiments of this disclosure, but the embodiments of this disclosure are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of this disclosure shall be considered equivalent substitutions and shall be included within the protection scope of this disclosure.
Claims
1. A method for preparing a nickel-iron alloy / yttrium oxide composite material supported on nickel foam, characterized in that, Includes the following steps: (1) According to the hydrothermal method, nickel foam supported nickel iron yttrium hydroxide precursor is synthesized by first dissolving 0.16~0.22 g nickel nitrate hexahydrate, 0.05~0.07 g ferrous acetate, 0.15~0.24 g yttrium nitrate hexahydrate and 0.26~0.30 g hexamethylenetetramine in a mixed solution of anhydrous ethanol and deionized water, respectively, and stirring evenly with a magnetic stirrer. Then, nickel foam is added to carry out hydrothermal reaction. The sample after hydrothermal reaction is washed and dried to obtain nickel iron yttrium hydroxide precursor. (2) Nickel-iron alloy / yttrium oxide NiFe / Y2O3 composite material is prepared by annealing heat reduction treatment. The nickel-iron yttrium hydroxide precursor is placed in a tube furnace and calcined in an atmosphere of 3%~10% H2 / Ar to convert it into nickel-iron alloy / yttrium oxide NiFe / Y2O3 composite material. The nickel-iron alloy / yttrium oxide composite material has a nanosheet morphology formed by interconnected nanoparticles. The average size of the nanoparticles in the composite material is 14 nm, and the double-layer capacitance of the composite material is 12.67 mF cm⁻¹. -2 .
2. The preparation method according to claim 1, characterized in that, In step (1), the hydrothermal reaction uses a mixed solution of deionized water and anhydrous ethanol, wherein the volume ratio of deionized water to anhydrous ethanol is 1:
1.
3. The preparation method according to claim 1, characterized in that, In step (1), the hydrothermal reaction temperature is 90~120 ℃ and the reaction time is 8~12 h.
4. The preparation method according to claim 1, characterized in that, In step (2), the precursor is subjected to the annealing treatment in an H2 / Ar atmosphere at a heating rate of 1~5 °C min. -1 The calcination temperature is 400~550 °C and the calcination time is 1~5 h. Nickel-iron hydroxide is transformed into NiFe alloy, yttrium hydroxide is transformed into Y2O3, and the precursor is transformed into NiFe / Y2O3 composite material.
5. A nickel-iron alloy / yttrium oxide composite material with nickel foam loading obtained by the preparation method according to any one of claims 1-4.
6. The application of the nickel-iron alloy / yttrium oxide composite material supported on foamed nickel according to claim 5, characterized in that, The composite material was used as a catalyst for electrochemical activation and testing.
7. The application of the nickel-iron alloy / yttrium oxide composite material supported on nickel foam according to claim 6, characterized in that, The composite material was used as a catalyst for electrochemical activation and testing, including the following steps: (1) The electrochemical test was performed in a standard three-electrode test system, wherein the nickel-coated nickel-iron alloy / yttrium oxide NiFe / Y2O3 composite material was directly used as the working electrode, and the area of the working electrode was 0.25~2 cm². 2 A carbon rod is used as the counter electrode, a silver / silver chloride electrode is used as the reference electrode, and a KOH solution with a concentration of 0.8~1.2 M is used as the electrolyte. (2) Before performing the electrochemical test, the working electrode is activated by cyclic voltammetry at a scan rate of 20-80 mVs. -1 The voltage scanning range relative to the reversible hydrogen electrode is 0 to -0.5 V, and the number of scans is 5 to 50. (3) The voltage scan range for polarization curve testing relative to the reversible hydrogen electrode is 0 to -0.8 V, and the scan rate is 5 mV s. -1 Electrochemical impedance spectroscopy (EIS) measurements were performed at a constant voltage of -0.15 V relative to the reversible hydrogen electrode, with a frequency range of 0.01 Hz to 100 kHz. For double-layer capacitance measurements, the voltage scan range relative to the silver / silver chloride electrode was -0.45 to -0.35 V, with scan rates of 20, 30, 40, 50, 60, 70, and 80 mV s. -1 .
Citation Information
Patent Citations
Self-supporting nickel-yttrium oxide electrocatalytic hydrogen evolution electrode and preparation method and application thereof
CN113774419A
Difunctional active electrode for hydrogen production by electrolysis of water
CN115323396A
Composite catalytic electrode for hydrogen evolution by electrolysis of water as well as preparation method and application of composite catalytic electrode
CN118621341A
Electrochemical hydrogen pumping coupled with catalytic membrane reactor and its applications
WO2025245447A1
KR20220103428A